2022
DOI: 10.1063/5.0087498
|View full text |Cite
|
Sign up to set email alerts
|

Combining localized orbital scaling correction and Bethe–Salpeter equation for accurate excitation energies

Abstract: We applied localized orbital scaling correction (LOSC) in Bethe-Salpeter equation (BSE) to predict accurate excitation energies for molecules. LOSC systematically eliminates the delocalization error in the density functional approximation and is capable of approximating quasiparticle (QP) energies with accuracy similar or better than the GW Green's function approach and with much less computational cost. The QP energies from LOSC instead of commonly used G0 W0 and ev GW are directly used in BSE. We show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 138 publications
0
18
0
Order By: Relevance
“…In BSE/G 0 W 0 , the dependence on the DFA starting point is in the range of 0.5 eV for predicting valence excitation energies and can even exceed 1.0 eV for predicting CT excitation energies. 59 It has been shown that BSE/G 0 W 0 based on range-separated functionals and tuned hybrid functionals provides more accurate excitation energies 32,60 than BSE/ G 0 W 0 based on GGA functionals. This dependence can be largely reduced by introducing self-consistency into the GW calculations, such as the eigenvalue-self-consistent GW (evGW) method, where the eigenvalues are iterated in G and W, the quasiparticle-self-consistent GW (qsGW) scheme,c 61,62 or the fully self-consistent GW (scGW) approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BSE/G 0 W 0 , the dependence on the DFA starting point is in the range of 0.5 eV for predicting valence excitation energies and can even exceed 1.0 eV for predicting CT excitation energies. 59 It has been shown that BSE/G 0 W 0 based on range-separated functionals and tuned hybrid functionals provides more accurate excitation energies 32,60 than BSE/ G 0 W 0 based on GGA functionals. This dependence can be largely reduced by introducing self-consistency into the GW calculations, such as the eigenvalue-self-consistent GW (evGW) method, where the eigenvalues are iterated in G and W, the quasiparticle-self-consistent GW (qsGW) scheme,c 61,62 or the fully self-consistent GW (scGW) approach.…”
Section: Introductionmentioning
confidence: 99%
“…63,64 It has been shown that the BSE/evGW approach provides an accuracy comparable to TDDFT for predicting valence excitations and significantly outperforms BSE/G 0 W 0 and TDDFT for predicting CT and Rydberg excitations. 38,59,65 The DFA dependence in BSE/evGW is largely washed out. 38,59,65 In practice, evGW calculations can converge within a few steps by using the linear mixing method.…”
Section: Introductionmentioning
confidence: 99%
“…29 G RS W RS provides consistent improvements over G 0 W 0 29 and has been combined with the Bethe−Salpeter equation to compute accurate excitation energies. 64 The concept of RS has also been successfully applied in the multireference DFT approach 65 to describe the static correlation in strongly correlated systems. The RS Green function shares similar thinking as the renormalized singleexcitation (rSE) in the random phase approximation (RPA) calculation for accurate correlation energies.…”
mentioning
confidence: 99%
“…G RS W 0 outperforms G 0 W 0 for predicting IPs with a small starting point dependence but fails to provide the unique solution to the QP equation for core states and has been combined with the Bethe–Salpeter equation to compute accurate excitation energies . The concept of RS has also been successfully applied in the multireference DFT approach to describe the static correlation in strongly correlated systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation